Perovskite With Tunable Active-Sites Oxidation State by High-Valence W for Enhanced Oxygen Evolution Reaction - Yan, Jiabiao; Xia, Mingkun; Zhu, Chenguang; Chen, Dawei; Du, Fanglin (Frontiers in Chemistry, 2022)
Perovskite oxides have been established as a kind of promising catalysts for alkaline oxygen evolution reaction (OER), because of their regulated non-precious metal components. However, the surface lattice amorphous during reaction gradually decreased the intrinsic activity and stability of catalysts. Herein, the precisely control tungsten atoms substituted perovskite oxides (Pr0.5Ba0.5Co1-xWxO3-δ) nanowires were developed by electrostatic spinning. The activity and Tafel slope were both depended on the W content in a volcano-like fashion, and the optimized Pr0.5Ba0.5Co0.8W0.2O3-δ exhibits both excellent activity and superior stability compared with other reported perovskite oxides. Due to the more outermost vacant orbitals of W6+, the electronic structure of cobalt sites could be efficiently optimized. Meanwhile, the stronger W-O bond could also significantly improve the stability of lattice oxide atoms to availably impede the generation of surface amorphous layers, showing good application value in alkaline water splitting.